Das Fernsehen unter dem Hakenkreuz . Television Under the Swastika - Unseen Footage from the Third Reich - Kloft, Michael (Lind, Elvira, 1999)
Duration: 00:54:00 This excellent documentary shows clips from 1935-1944. Clips include interview programs with Labor Minister Robert Ley, footage of the 1936 Olympics, light entertainment programs (vaudeville, etc.), plays, exercise shows, propaganda documentaries, cooking shows, and coverage of the 1938 Nuremberg rally. There's also a documentary of how amputee vets are being rehabilitated with artificial legs. It also interviews some of the German TV pioneers who explain how some of the early technology worked. In its stated mission - to imprint the image of the Führer onto every German heart - Nazi television proved a major disappointment. But its surviving footage - 285 rolls have been found so far offers an intriguing new window onto Hitler's Germany.